2008
DOI: 10.1038/npre.2008.2672.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic control of eukaryotic chromatin structure by recursive topological restraints

Abstract: Chromatin structure undergoes many changes during the cell cycle and in response to regulatory events. A basic unit of chromatin organization is the nucleosome core particle. However, very little is known about how nucleosomes are arranged into higher-order structures in vivo, even though the efficiency and precision of cell division imply high levels of structural organization. We propose abandoning the current paradigm of chromatin organization based on thermodynamics of the lowest energy state and replace i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…It will be very interesting to study whether the hemicatenane has preferential locations as a function of the nucleotide sequences at the junction. More generally, the method described here should allow one to begin testing the theoretical models that proposed a role for DNA hemicatenanes in the organization of the genome in loops and chromosomal domains, and a modulation of genetic expression as a function of the location of the loops along the genome sequence [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be very interesting to study whether the hemicatenane has preferential locations as a function of the nucleotide sequences at the junction. More generally, the method described here should allow one to begin testing the theoretical models that proposed a role for DNA hemicatenanes in the organization of the genome in loops and chromosomal domains, and a modulation of genetic expression as a function of the location of the loops along the genome sequence [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous work showed that four-stranded DNA structures formed in vitro by DNA fragments containing tracts of the poly(CA)·poly(TG) sequence (CA-microsatellites) consisted in DNA loops with a hemicatenane at their base [ 19 ] and were tightly bound by nuclear protein HMGB1 in vitro [ 20 , 21 ]. This led us to suggest that complex genomes might be organized in chromosomal loops maintained by topological DNA knots, possibly hemicatenanes, a hypothesis with original and interesting implications on the control of genome function during development and differentiation [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in the ability of the cell to maintain euchromatic regions and the transcriptional state of the genes residing therein could be as deleterious as the potential activation of developmentally silenced genes. Transcriptionally, active chromatin (euchromatin) is not, necessarily in an "open" conformation (Sapojnikova et al 2009), but is a compact 30-nm fiber (Bystricky et al 2004) that transiently opens up for transcription and may exist naturally in a high-energy conformation that is topologically constrained (Borek and Otwinowski 2008). If this model holds, basic chromatin (DNA plus nucleosomes) is in a compact structure allowing for accessory proteins and modifications to dictate what is heterochromatin and euchromatin.…”
Section: Chromatin Models Of Agingmentioning
confidence: 99%